2010
DOI: 10.1111/j.1365-2516.2010.02205.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoaneurysm in association with a knee endoprothesis operation in an inhibitor‐positive haemophilia A patient – treatment with local thrombin

Abstract: The clinical manifestations of severe haemophilia, an X-linked hereditary bleeding disorder, include spontaneous and trauma-related articular and muscular bleeds. Recurring bleeds in the target joints lead to haemophilic arthropathy and the need for endoprothesis. We report a case of a sudden intra-articular pseudoaneurysm formation in a synovial artery after endoprosthesis surgery of a knee. This event occurred in a haemophilia A patient with an inhibitor to factor VIII (FVIII).A 29-year-old man with a diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 3 publications
(8 reference statements)
0
14
0
Order By: Relevance
“…To our knowledge, to date, only eight cases of aneurysm following primary TKA [3540] and one following revision TKA [41] have been reported in patients with hemophilia. Saarela et al [38] applied local thrombin as treatment and obtained a satisfactory result, whereas in other reports, angiographic embolization was successfully performed. In one of our patients (case 4), thrombin injections were repeated three times without success, but complete obliteration was achieved with endovascular coiling technique.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, to date, only eight cases of aneurysm following primary TKA [3540] and one following revision TKA [41] have been reported in patients with hemophilia. Saarela et al [38] applied local thrombin as treatment and obtained a satisfactory result, whereas in other reports, angiographic embolization was successfully performed. In one of our patients (case 4), thrombin injections were repeated three times without success, but complete obliteration was achieved with endovascular coiling technique.…”
Section: Discussionmentioning
confidence: 99%
“…However, the haemarthrosis did not resolve, and 36 days postoperatively, a pseudoaneurysm of the left superior geniculate artery was found by angiography and percutaneously embolized. Saarela et al [11] have reported a pseudoaneurysm in association with a knee endoprothesis operation in an inhibitor-positive haemophilia patient treated with local thrombin.…”
Section: Ultrasound-guided Thrombin Injectionmentioning
confidence: 98%
“…A spontaneous haemarthrosis in the absence of anticoagulant medication or a bleeding disorder is a very rare complication after TKR [2]. In haemophilia, the most common cause of a haemarthrosis following TKR is the development of a pseudoaneurysm [6][7][8][9][10]. This complication is due to unrecognized injury of the peri-articular vessels.…”
mentioning
confidence: 99%
“…Failure to diagnose and treat it may lead to subsequent recurrence of bleeding. So far, only five reports on this complication have been published in the haemophilia literature [6][7][8][9][10]. Symptoms may include severe pain due to joint distension and swelling.…”
mentioning
confidence: 99%